ADUs and the Just City: How additional dwelling units can shape urban environments toward equitable outcomes in Canadian cities - Cipkar, Sarah (Frontiers in Sustainable Cities, 2023)
Using the model of a Just City the goal of this paper is to contribute to the discussion of additional dwelling units (ADUs) by connecting disparate literature on ADUs in North America to the body of spatial justice and posit a way forward that recognizes the drawbacks of a system of individual property ownership, while hypothesizing that more equitable outcomes could be achieved through the inclusion of ADUs within the private market system through government regulation. This paper argues that through the lens of equity, democracy, and diversity, ADUs have the potential to lead to more just outcomes within a privatized market housing system, where homeownership is both the dominant tenure and ideology. Accounting for the inequities of informal ADUs and the contradictions within a capitalist, financialised housing system, new pathways are conceived to both encourage and regulate the ADUs to ensure security of tenure and protection against market pressures.